Role of antioxidant systems, lipid peroxidation, and nitric oxide in postmenopausal osteoporosis - Ozgocmen, Salih; Kaya, Huseyin; Fadillioglu, Ersin; Aydogan, Rabia; Yilmaz, Zumrut (Springer, 2007)
In this study we assessed activities of antioxidant enzymes, lipid peroxidation end-products, and nitric oxide (NO) levels in women with postmenopausal osteoporosis (PMO). Relationship between oxidative stress parameters and NO levels with bone mineral density (BMD) and clinical variables influencing bone mass and health related quality of life measures was also investigated in women with PMO. Postmenopausal women (n = 87), aged 40-65, without previous diagnosis or treatment for osteoporosis and independent in daily living activities were included. BMD was measured at the lumbar spine and proximal femur using dual-X-ray absorptiometry (DXA). Erythrocyte catalase (CATe) enzyme activity, erythrocyte and plasma enzyme activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and lipid peroxidation end-product malondialdehyde (MDA) and nitrite/nitrate levels, by product of NO were studied. A total of 23 healthy non-porotic women were included as controls. Women with PMO had significantly lower erythrocyte CATe enzyme activity and higher erythrocyte malondialdehyde (MDAe) and erythrocyte nitric oxide (NOe) levels in comparison to controls whereas erythrocyte SODe and GSH-Px enzyme activity was similar. In plasma, osteporotic women had significantly higher SOD enzyme activity and higher MDA levels whereas similar GSH-Px enzyme activity and NO levels compared to non-porotic controls. Significant correlation was found between erythrocyte SODe, CATe enzyme activity and NOe levels with proximal femur BMD. Some of the quality of life scores as pain, mental, and social functions correlated with antioxidant enzyme activities and NO levels. Consequently, oxidative stress markers may be an important indicator for bone loss in postmenopausal women. Further researches assessing the oxidative stress markers and NO in bone tissue and changes with anti-osteoporotic drugs would be valuable to better understand the role of free radicals, antioxidants, and NO in the regulation of bone mass.
Keywords: antioxidant enzyme; malondialdehyde; nitric oxide; postmenopausal osteoporosis